ANALYSIS OF INFLUENCE OF REGIONAL ORIGINAL INCOME, CENTRAL GOVERNMENT TRANSFERS AND REGIONAL SHOPPING EFFICIENCY ON REGIONAL FINANCIAL INDEPENDENCE - Nasution, ANggi Pratama (Accounting and Business Journal, 2019)
This study aims to analyze the influence of local revenue variables, central government transfers, and efficiency of local expenditure, to the regional financial independence. This study collects empirical evidence. The population in this study were all districts / cities in North Sumatra Province period 2011- 2013, and the sample in this study amounted to 28 districts / cities in the Province of North Sumatra. In this thesis, the research writer uses causal associative research design. The sampling method in this research is by purposive sampling method. The type of data used by the author is secondary data and data processing is done by using the statistical program tool. Classical assumption tests used by writers include normality tests, multicollinearity tests, and heterocedasticity tests. While the research model is used by the authors is to use statistical analysis of multiple linear regression equations, as for hypothesis testing is done by simultaneous significance tests, partial significance tests, and coefficient determinant. Based on the results of research, it is known that the variables of original revenues, central government transfers, and efficiency of regional expenditure, simultaneously significantly influence to the regional financial independence. Partially, local revenue variables, central government transfers have a significant effect on local financial independence. However, the efficiency of local expenditure has no positive effect on local financial independence. and coefficient determinant. Based on the results of research, it is known that the variables of original revenues, central government transfers, and efficiency of regional expenditure, simultaneously significantly influence to the regional financial independence. Partially, local revenue variables, central government transfers have a significant effect on local financial independence. However, the efficiency of local expenditure has no positive effect on local financial independence. and coefficient determinant. Based on the results of research, it is known that the variables of original revenues, central government transfers, and efficiency of regional expenditure, simultaneously significantly influence to the regional financial independence. Partially, local revenue variables, central government transfers have a significant effect on local financial independence. However, the efficiency of local expenditure has no positive effect on local financial independence.